EVALUATION OF RADIATION SHIELDING INTEGRITY OF FABRICATED CONCRETE WITH SOME SELECTED AGGREGATE SIZES (FUDMA JOURNAL OF SCIENCES, 2023)
Shielding is regarded as one of the three ways of minimizing radiation exposure to the workers and members of the public. Concrete is the most available and cheap material used in shielding, though its integrity in shielding radiation depends on the materials used in its production and the choice of the materials also depends on the type of radiation to be shielded. Due to the rapid increase in the number of unregulated usages of radiation facilities in Nigeria and the lack of locally established concrete shielding data for construction of such facilities, it is imperative to carryout research to generate such data. In this work, the radiation shielding properties of fabricated concretes with aggregates sourced from indigenous granite gravels of sizes 10 mm, 15mm and 20 mm is presented. Gamma rays of energies 0.662MeV from 137Cs, 1.173Mev and 1.332MeV from 60Co were used to expose the concrete samples, and the radiation attenuation coefficients were determined using NaI (Tl) gamma ray detector with a Multi-Channel Analyser. The average linear attenuation coefficients of the concrete samples with aggregate sizes of 10mm, 15 mm and 20 mm were found to be 11.10 ± 0.02cm-1, 15.02 ± 0.03cm-1, 12.19 ± 0.03cm-1 for 137Cs source and 7.24 ± 0.07cm-1, 9.66 ± 0.07cm-1,  8.73 ± 0.07cm-1 for 60Co source respectively. The results showed that the concrete mix obtained using 15mm aggregate size attenuated the radiation much higher than that of 10mm and 20mm, and is a promising candidate for cheap gamma rays shielding.
Keywords: Radiation Shielding, Concrete, Aggregate size, attenuation coefficients